Escaping Dystopia : Rebuilding a Public Domain - McBride, Stephen, 1947- (Bristol University Press, 2022)
Overcoming crises and forging alternatives is the most pressing issue of our times. In this book, Stephen McBride explores the multiple crises defining neoliberalism, identifying the linkages between them, and argues for radical solutions to revive our increasingly dystopian political and economic world.